PENGARUH DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN SAHAM INDUSTRI REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Nida Latifah (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this study is to analyze and understand the influence of Debt to Equity Ratio, Return On Asset, and Net Profit Margin simultaneously or partially to the stock return of real estate and property industry listed in Indonesia Stock Exchange period 2013-2017. The nature of this study is correlational research. The population is real estate and property industry listed on the Indonesia Stock Exchange period 2013-2017. Samples of research as many as 7 companies of real estate and property industry obtained by purposive sampling technique. The object in this research is the company’s annual report period 2013-2017. Data collecting technique using documentation method, while data analysis technique using multiple linear regression analysis supported by classical assumption test. The result showed that partially variable Debt to Equity Ratio and Return On Asset to have influence toward stock return. Meanwhile variable Net Profit Margin doesn’t have influence toward stock return. While in simultaneous three independent variables Debt to Equity Ratio, Return On Asset, and Net Profit Margin to have influence toward stock return.